Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

Chapitre XVII Sexe Et Tempérament et Conclusion dans Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée - Mead, Margaret; Chevassus, Georges (Moeurs et sexualité en Océanie: au coeur des sociétés traditionnelles des îles Samoa et de Nouvelle-Guinée, 1963)
Dans le texte Adolescence à Samoa (1928), l'auteure soutient que l'adolescence n'est pas une étape nécessaire entre l'enfance et l'âge adulte. Dans le texte Trois sociétés primitives de Nouvelle-Guinée (1935), elle analyse, à partir de ses observations de terrain, les différences de caractère entre hommes et femmes.
Keywords: anthropologie; approches et analyses; corps; cours; discipline; océanie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques